Remarks on Captives and Warriors in an Old Bulgarian Collection of Miracle Stories - Hristov, Yanko M.; Kostadinova, Dafina (Studia Ceranea, 2023)
When scholars’ efforts are focused on the ethnic, religious and social diversity in certain parts of the Byzantine commonwealth during the middle ages, the hagiographic literature stands out as a key primary source. One such source is a voluminous early tenth-century collection of miracle stories titled A Tale of the Iron Cross. Its essential role when trying to uncover data, specific information and truths about Bulgaria’s medieval past is undeniable. A number of highly informative records have been found and are well-preserved within the covers of this impressive literary work. Many of them have been used repeatedly in various scholars’ academic initiatives and undertakings. However, other Tale’s records, regardless of their unique peculiarities and immeasurable contemporary information, still remain outside of the main research work when it comes to the subject matter of captivity and warfare.